2021
DOI: 10.1111/tbed.14260
|View full text |Cite
|
Sign up to set email alerts
|

Multisystemic lymphoplasmacytic inflammation associated with PCV‐3 in wasting pigs

Abstract: Porcine circovirus 3 (PCV-3) has been detected in diseased and healthy pigs of different ages. Several reports have associated the agent with reproductive failure and mummified and stillborn piglets. One report from North America has proposed a consistent potential association with postweaning disorders. Thus, the present case report aimed to describe the histopathological lesions and their association with the presence of PCV-3 genome in postweaning pigs showing growth-retardation and thrown-back ears. All af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…PCV3 was first detected in pigs with cardiac and multisystemic inflammation [4]. Thereafter, numerous pieces of evidence proved that PCV3 is associated with multiorgan lymphoplasmacytic periarteritis, lymphocytic myocarditis, lymphoplasmacytic meningoencephalitis, and/or PDNS [16,73,74]. Alomar et al reported the investigation of PCV3-infected pigs and found that there were no obvious gross lesions in viscera, but multiorganic moderate to severe lymphoplasmacytic periarteritis and arteritis were observed in artery, heart, kidney, spleen, portal arteriole, meninges, lung, and/or stomach, characterized by inflammatory infiltration of lymphoplasmacytes [16].…”
Section: Multisystemic Inflammation and Immune Responsesmentioning
confidence: 99%
See 4 more Smart Citations
“…PCV3 was first detected in pigs with cardiac and multisystemic inflammation [4]. Thereafter, numerous pieces of evidence proved that PCV3 is associated with multiorgan lymphoplasmacytic periarteritis, lymphocytic myocarditis, lymphoplasmacytic meningoencephalitis, and/or PDNS [16,73,74]. Alomar et al reported the investigation of PCV3-infected pigs and found that there were no obvious gross lesions in viscera, but multiorganic moderate to severe lymphoplasmacytic periarteritis and arteritis were observed in artery, heart, kidney, spleen, portal arteriole, meninges, lung, and/or stomach, characterized by inflammatory infiltration of lymphoplasmacytes [16].…”
Section: Multisystemic Inflammation and Immune Responsesmentioning
confidence: 99%
“…Thereafter, numerous pieces of evidence proved that PCV3 is associated with multiorgan lymphoplasmacytic periarteritis, lymphocytic myocarditis, lymphoplasmacytic meningoencephalitis, and/or PDNS [16,73,74]. Alomar et al reported the investigation of PCV3-infected pigs and found that there were no obvious gross lesions in viscera, but multiorganic moderate to severe lymphoplasmacytic periarteritis and arteritis were observed in artery, heart, kidney, spleen, portal arteriole, meninges, lung, and/or stomach, characterized by inflammatory infiltration of lymphoplasmacytes [16]. Furthermore, the connective tissue and adventitia around the artery intima were destroyed by inflammatory infiltration, smooth muscle cells showed mild to severe vacuolation and loss of cytoplasmic boundary, endothelial cells expanded into the lumen, and leukocytes adhered to the endothelium [16].…”
Section: Multisystemic Inflammation and Immune Responsesmentioning
confidence: 99%
See 3 more Smart Citations